Maternal left ventricular hypertrophy and diastolic dysfunction and brain natriuretic peptide concentration in early- and late-onset pre-eclampsia - Borges, V. T.M. [UNESP]; Zanati, S. G. [UNESP]; Peraçoli, M. T.S. [UNESP]; Poiati, J. R. [UNESP]; Romão-Veiga, M. [UNESP]; Peraçoli, J. C. [UNESP]; Thilaganathan, B. (Wiley, 2018)
Objective: Pre-eclampsia (PE) is associated with maternal cardiac remodeling and diastolic dysfunction. The aim of this study was to assess and compare maternal left ventricular structure and diastolic function and levels of brain natriuretic peptide (BNP) in women with early-onset (< 34 weeks' gestation) vs those with late-onset (≥ 34 weeks' gestation) PE. Methods: This was a prospective, cross-sectional, observational study of 30 women with early-onset PE, 32 with late-onset PE and 23 normotensive controls. Maternal cardiac structure and diastolic function were assessed by echocardiography and plasma levels of BNP were measured by enzyme immunoassay. Results: Early- and late-onset PE were associated with increased left ventricular mass index and relative wall thickness compared with normotensive controls. In women with early-onset PE, the prevalence of concentric hypertrophy (40%) and diastolic dysfunction (23%) was also significantly higher (both P < 0.05) compared with women with late-onset PE (16% for both). Maternal serum BNP levels were significantly higher (P < 0.05) in women with early-onset PE and correlated with relative wall thickness and left ventricular mass index. Conclusions: Early-onset PE is associated with more severe cardiac impairment than is late-onset PE, as evidenced by an increased prevalence of concentric hypertrophy, diastolic dysfunction and higher levels of BNP. These findings suggest that early-onset PE causes greater myocardial damage, increasing the risk of both peripartum and postpartum cardiovascular morbidity. Although these cardiovascular effects are easily identified by echocardiographic parameters and measuring BNP, further studies are needed to assess their clinical utility. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: brain natriuretic peptide; cardiac hypertrophy; diastolic function; early-onset pre-eclampsia; late-onset pre-eclampsia; PE